Proof of Concept and Preliminary Results of Gas Detection by Measuring the Admittance at the Resonance and Anti-resonance of an Uncoated CMUT - Iglesias, Luis; Shanmugam, Priyadarshini; Michaud, Jean-François; Alquier, Daniel; Certon, Dominique; Dufour, Isabelle (Frontiers in Mechanical Engineering, 2020)
Functionalized films are commonly used in gas sensing to target a particular gas. This is due, in part, to their usually high capability to detect very low concentrations and their high selectivity. However, their poor stability over time remains a challenge when dealing with applications that require the sensing to remain reliable without frequent recalibration. For this reason, uncoated gas sensors have become increasingly popular regardless of their lower sensitvity and their often non-selective characteristics. There exist different approaches for gas sensing without a functionalized film. One possibility is to use an uncoated resonating sensor and tracking its resonant properties which depend on its surrounding environment. The easy integration capability of capacitive micromachined ultrasonic transducers (CMUTs) makes them great candidates for uncoated gas sensing. Moreover, they are able to reach very high resonant frequencies and, therefore, allow for a shorter response time. In this article, a method to detect gas by following the value of the admittance of an uncoated silicon nitride CMUT array at either the resonant or at the anti-resonant frequency is presented and tested. This chemical detection is purely based on the change of the physical properties of the gas mixture (the mass density and the viscosity). A general model describing the impact of the electrical and mechanical properties of the CMUT in the sensitivity is presented, validated and applied to carbon dioxide and methane detection.